Young and adult patients with gaming disorder: Psychiatric co-morbidities and progression of problematic gaming - Hofstedt, Annika; Söderpalm Gordh, Anna (Frontiers in Psychiatry, 2024)
BackgroundPrevious research suggests age-dependent differences in the progression of addiction, and evidence is accumulating, showing that an early initiation of gaming increases the risk for addiction. With the recent introduction of gaming disorder (GD) as a psychiatric diagnosis, there is a need to extend the knowledge of the clinical characteristics of patients seeking treatment for GD of all age groups. Compared to adolescents and young adults, less is known about treatment-seeking adults. This study aimed to investigate whether there are clinically relevant age-dependent differences among patients seeking treatment for GD.MethodParticipants were recruited among patients seeking treatment and fulfilling diagnosis for GD at an outpatient clinic specialized in the treatment of GD. During the study period, 142 patients went through assessment for GD at the clinic, 37 did not fulfill the diagnosis for GD, and 36 declined participation, leaving a sample of 69 patients (age range = 15–56) for analysis. The sample (men, n = 66; women, n = 3) was divided in two age groups: adolescents and young adults (25 years or younger) and adults (26 years or older). Gaming-related data and information about psychiatric co-morbidity was collected through structured clinical interviews and questionnaires.ResultsThe adolescents and young adults (AYAs) reported a more rapid progression into problematic gaming than the adult group. The younger group developed problematic gaming four years faster than the adults. We also observed comparable clinical profiles in both groups. Both age groups had similar levels of GD as well as symptoms of psychiatric co-morbidities including possible attention deficit hyperactivity disorder (ADHD), autism spectrum disorders (ASD) and problematic gambling. We also noticed that half of our study population consisted of adults.ConclusionWith the increasing prevalence of gaming in all age groups, it is unknown how the occurrence of GD will develop in different stages of life. We conclude that the adolescents and young adults had almost double as fast progression to problematic gaming than the adult group, highlighting the need for preventive strategies. The similarity in clinical profiles indicates that treatments with the same type of interventions could be offered to both age groups.